Identity-based group key management scheme for space networks - LUO Chang-yuan; LI Wei; HUO Shi-wei (Tongxin xuebao)
The available group key management schemes are not suitable for space networks.Aiming at the problem,an identity-based space networks group key management scheme was proposed.It constructed a service nodes set using sat-ellite nodes to assist multicast group with calculating and broadcasting common parameters,and resolved the problem of imbalance consumption.The service node providing service for the same group was dynamic and changeable,which could avoid single-point failure.The proposed scheme can achieve security requirements and has less calculating,storing and communicating expense compared with available schemes.